Instituting a Curriculum for Cardio-Obstetrics Subspecialty Fellowship Training - Anum S. Minhas; Sarah A. Goldstein; Arthur Jason Vaught; Jennifer Lewey; Cary Ward; Steven P. Schulman; Erin D. Michos (Methodist DeBakey Cardiovascular Journal)
Maternal mortality is rising in the United States, and cardiovascular disease is the leading cause. Adverse pregnancy outcomes such as preeclampsia and gestational diabetes heighten the risk of cardiovascular complications during pregnancy and the peripartum period and are associated with long-term cardiovascular risks. The field of cardio-obstetrics is a subspecialty within adult cardiology that focuses on the management of women with or at high risk for heart disease who are considering pregnancy or have become pregnant. There is growing recognition of the need for more specialists with dedicated expertise in cardio-obstetrics to improve the cardiovascular care of this high-risk patient population. Current recommendations for cardiovascular fellowship training programs accredited by the Accreditation Council for Graduate Medical Education involve establishing core competency in the knowledge of managing heart disease in pregnancy. However, little granular detail is available of what such training should entail, which can lead to knowledge gaps. Additionally, dedicated advanced subspecialty training in this area is not commonly offered. Multidisciplinary collaborative teams have been shown to improve outcomes in cardiac patients during pregnancy, and cardiovascular fellows-in-training interested in cardio-obstetrics should have the opportunity to participate in and contribute to a pregnancy heart team. In this document, we describe a proposed specialized cardio-obstetrics training pathway that could serve to adequately prepare trainees to competently and comprehensively care for women with cardiovascular disease before, during, and after pregnancy.